Dismantling the medieval early modern perceptions of a female convent's past - Vanderputten, Steven 1976- (Brepols, 2021)
Dismantling the Medieval' studies the paradoxical relationship of the early modern canonesses of Bouxières abbey with the medieval past of their institution. While various documentary, material, spatial, and immaterial legacies of that past remained a crucial presence in the convent?s narrative of self, the canonesses also used and manipulated them to pursue and justify drastic changes in their organization and lifestyle. Thanks to an unusually rich and varied body of evidence, we are able to reconstruct in unprecedented detail this elite convent?s memory culture over a period of more than two centuries. We see how it was expressed and how it evolved, and what were the factors that drove forward its development. The resulting image of a highly flexible memorial culture helps us to explain how and why it lived on throughout many crises and transformations, including even the abbey's dissolution in 1791.
Keywords: Kloster Bouxières-aux-Dames; Geschichte